2019
DOI: 10.1016/j.jep.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Linking resource supplies and price drivers: Lessons from Traditional Chinese Medicine (TCM) price volatility and change, 2002–2017

Abstract: Ethnopharmacological relevance: Worldwide, one of the drivers of substitution and adulteration is the cost of the natural resources (plants, animals, fungi) that are ingredients of traditional medicines. Relatively few studies have been done that link prices of traditional medicine ingredients to what drives changes in price, yet this is an important topic. Theoretically, prices have been widely considered as an economic indicator of resource scarcity. Rare, slow growing medicinal plants sell for high prices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…In the qualitative interviews, we found a reduced tendency over time to purchase caterpillar fungus as a gift, as also observed byCunningham and Long (2019) who reported a dramatic caterpillar fungus price decrease as a result of the anti-corruption campaigns of President Xi Jinping.2 The survey was not broken down below the level of province (prefectural or county levels) in China, as there is little evidence, in either the literature or the authors' experiences, that consumers have any such detailed perceptions of origin.3 "Green food" refers to food produced and processed under the principles of sustainable development and certified by the China Green Food Development Center under the Ministry of Agriculture (seeSanders, 2006).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…In the qualitative interviews, we found a reduced tendency over time to purchase caterpillar fungus as a gift, as also observed byCunningham and Long (2019) who reported a dramatic caterpillar fungus price decrease as a result of the anti-corruption campaigns of President Xi Jinping.2 The survey was not broken down below the level of province (prefectural or county levels) in China, as there is little evidence, in either the literature or the authors' experiences, that consumers have any such detailed perceptions of origin.3 "Green food" refers to food produced and processed under the principles of sustainable development and certified by the China Green Food Development Center under the Ministry of Agriculture (seeSanders, 2006).…”
supporting
confidence: 81%
“…The product is widely distributed in alpine grasslands on the Tibetan Plateau and the Himalayan mountains in India, Nepal, and Bhutan (Li et al, 2011(Li et al, , 2021, harvested by hundreds of thousands of households (Pouliot et al, 2018;Sulek, 2019) and comprises one of the most important sources of income for high-altitude communities (Sulek, 2019;Timmermann & Smith-Hall, 2019;Winkler, 2009). The product was previously used in local medicinal practices and Traditional Chinese Medicine (Cunningham & Long, 2019), and current demand is driven by the rapidly growing middle-class in China that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often a large number of species are traded in herbal markets (Ahmad et al 2018;Hoareau and DaSilva 1999), which in turn are influenced by ecological conditions, socio-economic features, development strategies and transportation systems (Botha et al 2004). The herbal business is quickly increasing globally (Kanwal and Sherazi 2017;Cunningham and Long 2019). Europe alone imports about US$ 1 billion worth in medicinal and aromatic plants annually from Asia and Africa (Sher and Hussain 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have confirmed that C. militaris has many striking bioactivities such as immunomodulatory (Liu et al., 2016), antitumor (Jo, Jang, Yang, Jang, & Park, 2020), anti‐aging(Ji, Jia, Li, Wang, & Cai, 2009), antioxidant (Chen, Wu, & Huang, 2013), anti‐inflammatory (Smiderle et al., 2014), anti‐influenza effects (Ohta et al, 2007), antifibrotic (Nan, Park, Yang, Song, Ko, & Sohn, 2001) and so on. However, the popularity and high demand for C. sinensis and C. militaris has led to the scarcity of them, leading to their classification as protected endangered species (Cunningham & Long, 2018).…”
Section: Introductionmentioning
confidence: 99%